Pre-spawning snout-gripping behaviors of gymnothorax pictus and gymnothorax thyrsoideus (muraenidae) in captivity - Loh, Kar Hoe; Chen, Hong Ming (National Taiwan Ocean University, 2018)
The main focus of this study has been on the distinctive pre-spawning snout-gripping behaviors and mate choice of two moray species (Gymnothorax pictus and G. thyrsoideus). The behavior of snout-gripping means that the male grips the female’s snout with its jaws. It is the most distinctive behavior to confirm the success of mating pair formation naturally and was rarely described on moray eels or other coral reef fishes. The reproductive behaviors of the two moray species were also first observed and photographed in the laboratory aquaria. Over 22 reproductive events including 9 spawning events by 28 adult individuals of G. pictus were recorded. Eight sequential behaviors were recorded in the successful spawning events of G. pictus searching, courting, inviting, snout-gripping, rushing toward the water surface, turning around, spawning, separating and settling to the bottom. G. thyrsoideus also exhibited similar pre-spawning behaviors as G. pictus, but showed more aggressive behaviors between the males than G. pictus. Courtships and mating affairs occurred about 23 times by 32 adult individuals of G. thyrsoideus, but without spawning. Both species mated mainly between a female and a male at night (8:00PM-2:00AM). It only took a shorter time for G. pictus to go from snout-gripping to spawning (3-7 seconds), but a longer time for G. thyrsoideus to go from snout-gripping to separating (35-43 seconds).